1996
DOI: 10.1029/96je03305
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐silicate fractionation in the surface dust layers of accreting planetesimals: Implications for the formation of ordinary chondrites and the nature of asteroid surfaces

Abstract: Some of the most primitive solar system materials available for study in the laboratory are the ordinary chondrites, the largest meteorite class. The size and distribution of the chondrules (silicate beads) and metal, which leads to the definition of the H, L, and LL classes, suggest sorting before or during aggregation. We suggest that meteorite parent bodies (probably asteroids) had thick dusty surfaces during their early evolution that were easily mobilized by gases evolving from their interiors. Density an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 74 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…All rely on the physical properties of metal and silicates, such as magnetism, ductility, grain size, and density (Donn and Sears, 1963;Whipple, 1966;Harris and Tozer, 1967;Orowan, 1969;Larimer and Anders, 1970;Rowe et al, 1972;Dodd, 1976a;Dodd, 1976b;Weidenschilling, 1977). More recently, Huang et al (1996) and Akridge and Sears (1999) suggested that gravity and density sorting in a thick regolith of a small asteroid would produce metalsilicate separations of the sort observed in the ordinary chondrites. These physical processes would separate the iron from the silicates without undergoing chemical changes and would not result in the isotopic fractionations observed in Fig.…”
Section: Chemical Classesmentioning
confidence: 94%
“…All rely on the physical properties of metal and silicates, such as magnetism, ductility, grain size, and density (Donn and Sears, 1963;Whipple, 1966;Harris and Tozer, 1967;Orowan, 1969;Larimer and Anders, 1970;Rowe et al, 1972;Dodd, 1976a;Dodd, 1976b;Weidenschilling, 1977). More recently, Huang et al (1996) and Akridge and Sears (1999) suggested that gravity and density sorting in a thick regolith of a small asteroid would produce metalsilicate separations of the sort observed in the ordinary chondrites. These physical processes would separate the iron from the silicates without undergoing chemical changes and would not result in the isotopic fractionations observed in Fig.…”
Section: Chemical Classesmentioning
confidence: 94%
“…In many, the ice was melted by a bulk heating process, due most probably to the decay of short halflife radionuclides such as 26A1 (Grimm and McSween, 1989). The resulting water underwent various reactions, most of which were strongly exothermic (Grimm and McSween, 1989;Coker and Cohen, 1998), with the initial silicate mineral assemblage to produce phyllosilicates and liberate significant quantities of, mainly, hydrogen (Browning and Bourcier, 1996; note that other aspects of the role of degassing of ordinary chondrite parent bodies have also been discussed by Huang et al, 1996). The exothermic nature of the strengths of the asteroid materials, causing fractures to form.…”
Section: Models Of the Development Of Asteroid Bulk Densities Collisimentioning
confidence: 99%
“…Only if the metal and chondrules were comparable in size would the denser metal grains fall in the regolith (Chiba et al, 1980;Huang et al, 1996b). If the flow rate required to suspend the large components exceeds twice the terminal flow velocity of one of the finer components (e.g., the fine-grained matrix), then the fine material will be lifted out of the column entirely ("elutriated"), much like dust is lifted from the surface of comet nuclei (Griin and Jessberger, 1990).…”
Section: Premise I: Primary Parent Bodies Were Ci-like In Compositionmentioning
confidence: 99%